The Significance of Height on Median and Ulnar Nerves Conduction Parameters in Male Subjects - Jassim, Nawrass; Abdulateef, Hayder; Noel, Khalida I. (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Many physiological factors including body temperature, age, height, and gender of the subject affect the nerve conduction parameters (both sensory and motor nerves), so attention should be played for these factors during the evaluation of the nerve function to avoid the false results and later on the false diagnosis of the disease. AIM: The aim of the study was to observe the power of height on median and ulnar nerves conduction parameters (both motor and sensory fibers) in male subjects. METHODS: Seventy healthy males aging 18–60 years were incorporated in the study, for them, motor and sensory nerve conduction study of both ulnar nerve and median nerve was done using NIHON KHODEN machine. RESULTS: There was a significant positive correlation between height and the latency of ulnar sensory nerve (r = 0.29, p = 0.01, and odd’s ratio was 1.6). At the same time, there was significant negative power of height on median and ulnar sensory amplitude (r = −0.32, p = 0.007 and r = −0.28, p = 0.018, respectively). CONCLUSION: The consequence of height on median and ulnar nerve conduction parameters (motor and sensory) is crucial for interpretation the data and later on the diagnosis of the diseases.